2011
DOI: 10.1029/2010jb007891
|View full text |Cite
|
Sign up to set email alerts
|

Plastic anisotropy and fabric evolution in sheared and recrystallized quartz single crystals

Abstract: [1] The effect of a lattice preferred orientation on the flow strength of quartz aggregates dynamically recrystallized from single crystals of synthetic quartz was investigated using general shear experiments in a Griggs apparatus. Experiments were conducted at shear strains (g) up to 5 at a temperature of 900°C, confining pressure of 1.5 GPa, and shear strain rate of 10 −5 s −1 . Three starting orientations of crystal were used, to activate three slip systems: basal hai, prism [c], and prism hai, although sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 47 publications
(68 reference statements)
6
52
0
Order By: Relevance
“…Y-max textures, related to the activity of prism <a> slip, are consistent with upper greenschist-lower amphibolite facies deformation, assuming normal geologic strain rates and water content (e.g., Schmid & Casey, 1986). In this domain large relic grains were compliant during deformation developing a high aspect ratio and a preferred orientation parallel to the foliation, as it is expected for grains with c axis parallel to Y under conditions of dominant prism <a> slip (e.g., Ceccato et al, 2017;Muto et al, 2011). Two major mechanisms are believed to have controlled the development of such diverse microstructures: (1) grain-scale strain partitioning leading to a completely different microfabric evolution within the different domains and (2) fluid ingress and fluid-rock interaction, as documented by the abundant pitted grain boundaries, trails of fluid inclusions, and secondary phases trapped in quartz ( Figure 5; e.g., Drury & Urai, 1990;Mancktelow et al, 1998;Mancktelow & Pennacchioni, 2004).…”
Section: Grain-scale Strain Partitioning In the Different Domainssupporting
confidence: 63%
See 1 more Smart Citation
“…Y-max textures, related to the activity of prism <a> slip, are consistent with upper greenschist-lower amphibolite facies deformation, assuming normal geologic strain rates and water content (e.g., Schmid & Casey, 1986). In this domain large relic grains were compliant during deformation developing a high aspect ratio and a preferred orientation parallel to the foliation, as it is expected for grains with c axis parallel to Y under conditions of dominant prism <a> slip (e.g., Ceccato et al, 2017;Muto et al, 2011). Two major mechanisms are believed to have controlled the development of such diverse microstructures: (1) grain-scale strain partitioning leading to a completely different microfabric evolution within the different domains and (2) fluid ingress and fluid-rock interaction, as documented by the abundant pitted grain boundaries, trails of fluid inclusions, and secondary phases trapped in quartz ( Figure 5; e.g., Drury & Urai, 1990;Mancktelow et al, 1998;Mancktelow & Pennacchioni, 2004).…”
Section: Grain-scale Strain Partitioning In the Different Domainssupporting
confidence: 63%
“…A classic example is represented by sheared quartz-feldspar aggregates at midcrustal conditions, where quartz typically recrystallizes and feldspar forms fractured porphyroclasts (Tullis et al, 1990(Tullis et al, , 2000Vernon & Flood, 1988). However, many studies, focused on quartz monomineralic aggregates, highlighted the complex role played by grain-scale strain partitioning in assisting semibrittle deformation in quartz (van Daalen et al, 1999;Muto et al, 2011;. However, many studies, focused on quartz monomineralic aggregates, highlighted the complex role played by grain-scale strain partitioning in assisting semibrittle deformation in quartz (van Daalen et al, 1999;Muto et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Similar recrystallized quartz fabrics have been reported in previous experiments on quartz deformed to comparable strains, both in quartzites [ Tullis et al ., ; Stipp et al ., ; Heilbronner and Tullis , ] and quartz single crystals [ Vernooij et al ., ; Muto et al ., ]. The rapid evolution with increasing strain to the strong Y axis maximum (Figure d) has been interpreted to result from GBM recrystallization [ Heilbronner and Tullis , ; Muto et al ., ]. The uncontoured pole figure diagram from the highest‐strain experiment reveals a faint cross girdle of c axis orientations indicative of minor slip on the rhomb and basal planes (Figure d).…”
Section: Resultsmentioning
confidence: 97%
“…GBM could explain the strongly serrated form and complex 3D intergrowth of crystals. In addition, recent experiments by Muto et al [2009], made under conditions in which recrystallization occurs by subgrain rotation and rapid grain boundary migration, have shown that GBM can completely change an initial CPO. However, support for this interpretation is not very convincing for the following reasons: (i) many WDV do not contain a population of grains well oriented for prism hai slip that could grow at the expense of the dominant population of poorly oriented crystals, (ii) the strain window for complete CPO replacement seems too small (g < 1), and (iii) the CPO of WDV with a strong peripheral maximum close to the X axis is present in veins that do not show pervasive GBM microstructures (Figure 1a).…”
Section: The Cpo Evolution Of the Adamello Quartz Veinsmentioning
confidence: 99%